Determinants of Foresight Maturity in SME Enterprises of Poland - Anna Kononiuk (Foresight and STI Governance)
The complication of the business environment, the growth of uncertainty, and the dynamics of change significantly affect strategic planning in business. Foresight research used in a company serves as a link between the volatility of the surrounding environment, possible expansion prospects, and an enterprise’s strategy and tactics. Based on data from Poland, this article examines the main factors that determine the readiness of small and medium-sized enterprises (SMEs) to navigate a variety of paths into the future (foresight maturity). This study uses an integrated approach, that integrates concepts of foresight maturity, dynamic capabilities, and corporate foresight. It relies upon a sample of over 500 Polish manufacturing SMEs, which is representative in terms of size, type, sector, and geography of activities. Using a 28-criteria assessment tool, it was found that the level of foresight maturity of a company most often depends on the size, type, and geographical coverage of markets. Involving stakeholders in the development of corporate strategies, scanning the micro- and macro-environment of the enterprise using a variety of information sources, improving skills in working with foresight tools as well as fostering other dynamic capabilities allow companies to gain lasting competitive advantages in a changing and unpredictable business landscape.